Pertanggungjawaban Pelaku Usaha Terhadap Pemenuhan Hak Konsumen Festival Musik yang Dibatalkan oleh Panitia Penyelenggara - Parawasansa, Anisa Umi Sya’ ada; Edhi Mahanani, Anajeng Esri (Universitas Ekasakti, 2023)
A music festival is a public music celebration that is held directly at a specified location and a large number of spectators or visitors are held in an arranged manner. In its implementation, there are still some non-fulfillment of consumer rights that are violated by business actors, causing losses to consumers who have purchased festival tickets. The implementation of music festivals does not always run smoothly and well so that there are often deficiencies that result in dissatisfaction or non-fulfillment of the rights of event visitors as consumers of music festival events. The purpose of this study is to find out about legal arrangements for fulfilling consumer rights in organizing music festivals. The type of research used is normative juridical research. Primary and secondary sources of data and legal materials were obtained from legislation related to legal issues, namely Law no. 8 of 1999 concerning Consumer Protection, publications with the theme of consumer protection, as well as journals that discuss consumer protection for non-fulfillment of rights by business actors.